(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This paper explores the vital role of literature in promoting tolerance and cross-cultural understanding in an increasingly interconnected world. Through the analysis of scholarly research and theoretical frameworks, it demonstrates how literature fosters empathy, challenges stereotypes, and encourages respect for cultural diversity. The study highlights the importance of inclusive literary representation and the use of multicultural texts in education to build intercultural competence. It also addresses the potential risks of misrepresentation and emphasizes the need for critical reading. Ultimately, the paper concludes that literature is not only a mirror of society but also a transformative tool capable of shaping more inclusive and tolerant communities.